Therapeutic care for refugees : no place like home - Papadopoulos, Renos K. (Tavistock Clinic series., 2002)
This volume addresses the complexities involved in attending to the mental health of refugees. It covers theory and research as well as clinical and field applications, emphasising the psychotherapeutic perspective. It explores the delicate balance between accepting the resilience of refugees whilst not neglecting their psychological needs, within a framework that avoides pathologising their condition.